Adaptive decision directed impulse noise mitigate in power line communication. Issue 3 (1st May 2018) - Tan, Zhouwen; Liu, Hongli
Abstract : Impulse noise (IN) is the main cause of performance degradation in high‐speed power line communication systems. Traditional methods mainly focus on manually setting a fixed blanking threshold to mitigate the corresponding IN. However, the fixed threshold cannot adapt to the time‐varying IN efficiently. To solve this problem, an adaptive IN‐mitigation system is proposed based on orthogonal frequency division multiplexing in a time‐varying IN channel. The characteristics of IN are pre‐evaluated by the method of moment estimation. Moreover, the adaptive threshold is efficiently solved in closed form according to the IN characteristics. In addition, an adaptive iterative IN‐mitigation block is designed to leverage the performance of the receiver. For the number of iterations, a look‐up table is constructed according to the IN characteristics. The experimental results show that the proposed method achieves performance balance in weak, moderate, and heavy IN environments simultaneously. It is noted that the bit error rate significantly decreases with an increment in E b / N 0 .